Home Environment, Mental Health and Academic Achievement Among Secondary School Students: The Impact of Home Environment and Emotional Maturity on Academic Achievement and Mental Health in Secondary School Students (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Academic achievement has great importance for both the student, andthose around him/her. There can be no doubt that it is affected by two broadfactors:   subjective factors or individualfactors and objective factors or environmental factors. The subjective factorsare related to the individual himself and the objective factors pertain to theenvironment of the individual. Emotional maturity is one of the individual andnon-cognitive factors that may affect the academic achievement of the students.The impact of home environment and academic achievement on mental health wereinvestigated in a Secondary school students sample consisting of 300participants, 150 of whom were females and 150 were males. Results revealedthat mean value of mental health of girls is 74.7 and boys is  70. Therefore, this was revealed afteranalyses that the mean value of mental health of girls is more in comparison toboys.